Access to water and COVID-19: A regression discontinuity analysis for the peri-urban areas of metropolitan Lima, Peru - Andrés Gómez-Lobo; Mauro Gutiérrez; Sandro Huamaní; Diego Marino; Tomás Serebrisky; Ben Solís Sosa (Inter-American Development Bank (IDB), 2022)
This paper presents the results of a quasi-experimental study using information collected through a survey conducted in peri-urban areas of Metropolitan Lima between October and November 2021. The survey was applied to households residing close to and on both sides of the geographic boundary of piped water supply. Our work finds that access to piped water was associated with a reduction in the probability of a COVID-19 infection. Furthermore, the model used shows heterogeneous effects that suggest that it is not enough for a household to be connected to the water supply network, but that a minimum consumption endowment must also be guaranteed. The results should be interpreted by taking into consideration the limitations of the information. These results highlight the need for investment in infrastructure to close access gaps and the importance of ensuring quality and affordable services for the population.
Keywords: L95; I14; I15; I10; I18; 330; water; sanitation; COVID-19; health; regression discontinuity; Lima; Peru